Reliability of YouTube videos on the management of orthodontic emergencies during COVID-19 pandemic: A quantitative and qualitative analysis - Zaki Hakami; Satish Vishwanathaiah; Hussain Y. A. Marghalani; Ahmed M. Bokhari; Mohammad Raji Alrwuili; Abdulaziz Abdullah S. Barashid; Mohammad Sawadi; Prabhadevi C. Maganur (Wolters Kluwer Medknow Publications, 2024)
OBJECTIVES: To assess the content of YouTube videos on the management of orthodontic emergencies during the COVID-19 pandemic. MATERIALS AND METHODS: YouTube was systematically searched using the keywords "orthodontic emergency," "orthodontic homecare," "braces emergency," and "braces homecare." The first 100 videos for each keyword were assessed. The upload source, number of views, likes and dislikes, duration, and global quality score were extracted. Home and clinical advice reliability was evaluated using the reliability score (DISCERN) according to the COVID-19 orthodontic emergencies protocol published by the British Orthodontic Society. RESULTS: The majority of the videos were found to be poor quality. Home care advice showed higher reliability than clinical advice. Orthodontic emergency videos uploaded by healthcare professionals had higher reliability. CONCLUSION: Many types of orthodontic emergencies have received little attention on YouTube, and more useful and reliable educational videos should be uploaded in the event of future pandemics.